Calcium Intake Requirements Along the Life Cycle and Associated Factors - Rubio-Navarro, Lorena; Perez-Torrero, Esther (Current Nutrition & Food Science, 2015)
Calcium is an essential nutrient required for various biological functions. Several studies have shown an association between calcium deficiencies and chronic diseases such as osteoporosis. The aim of this review was to collect relevant information about the importance of healthy bones, general requirements of calcium intake and special requirements during pregnancy and the lactation period. The risk of a fracture in elderly people is related to inadequate intake and metabolism of calcium during life that can affect the bone structure. In addition, some plant sources have high calcium content, proving the requirements of calcium especially to people with intolerance to common sources of calcium like milk. The effects of a balanced nutrition and physical activity during early life have long lasting beneficial effects in bone health in adulthood.
Keywords: osteoporosis